PENGEMBANAN SUMBER BELAJAR E-LEARNING - -, Srihartini (Widya Wacana: Jurnal Ilmiah, 2014)
The benefit of E-learning program design is its ease so that  it may use various learning resource.  Webs provides unlimited access of material to enrich contents developed especially fo learning program.  An established and clear as well as goal-oriented learning design is needed to make E-learning more focus , effective and efficient.   Keywords: E-Learning, program design, learning program